Agricultural research and productivity growth in India - Evenson, Robert E.; Pray, Carl E.; Rosegrant, Mark W. (International Food Policy Research Institute, 1999)
India’s investments in agricultural research, extension, and irrigation have made it one of the largest publicly funded systems in the world. But some policymakers who perceive that the benefits to research may be declining are advocating a cut back on public spending on research. This research report, which examines the effects of research and development on productivity in India, finds that India is still benefiting from these investments. The main sources of agricultural productivity growth in India during 1956–87 were public agricultural research and extension; expansion of irrigated area and rural infrastructure and improvement in human capital were also important contributors. The report also shows that the public benefits from private research can be sub stantial, indicating that private firms capture only part of the real value of improved inputs through higher prices. Private agricultural research accounted for more than 10 per cent of growth of total facto productivity (TFP) during 1956–87, and in 1966–75, when India was more open to foreign technology, private research contributed 22 per cent of productivity gowth. Industrial policy and technology policy, including intellectual property rights policy, will require careful evaluation and reform in order to encourage private investment in agriculture. Even so, Pray and Rosegrant argue that barriers to technology transfer should be removed in order to stimulate technology transfer and growth. Nevertheless, public investment in agricultural research will likely retain its primary role. Contrary to concerns that growth in TFP has decreased over time, the report finds that during 1977–87, the period when the results in regions that adopted high-yielding varieties early on could be expected to taper off, TFP growth was 50 per cent higher than before the Green Revolution and 17 per cent higher than in the early years of the Green Revolution, indicating that gains are far from over. The rates of return to public agricultural research are high, and it appears that the government is under investing in agricultural research. Expanding public investment in research and extension would lead to even greater gains. (Forward by Per Pinstrup-Andersen)